2011
DOI: 10.3109/00365548.2011.570785
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of combined viral and bacterial infection in patients with community-acquired pneumonia

Abstract: Patients infected with a virus and a bacterial pathogen more often develop severe CAP and have a longer hospitalization than those with a bacterial etiology alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
3
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 200 publications
(406 reference statements)
1
51
3
3
Order By: Relevance
“…In the study of Johnstone et al; mortality, duration of hospitalization and acceptance rates to intensive care units were similar for both groups [29]. However, in other studies, concomitance of rhinovirus and pneumococci were found to be associated with severe pneumonia [6,13] and it was reported that patients infected with a virus and a bacterial pathogen more often develop severe CAP with a longer hospitalization [32]. In our study, further evaluation could not be performed due to the low number of patients.…”
Section: Discussionmentioning
confidence: 85%
“…In the study of Johnstone et al; mortality, duration of hospitalization and acceptance rates to intensive care units were similar for both groups [29]. However, in other studies, concomitance of rhinovirus and pneumococci were found to be associated with severe pneumonia [6,13] and it was reported that patients infected with a virus and a bacterial pathogen more often develop severe CAP with a longer hospitalization [32]. In our study, further evaluation could not be performed due to the low number of patients.…”
Section: Discussionmentioning
confidence: 85%
“…It remains unclear whether a bacterial coinfection is associated with more severe disease. Some previous reports (1,4,34) have shown that viral-bacterial coinfections were associated with more severe clinical disease as measured by the Pneumonia Severity Index (35), and/or longer hospital stays, but other studies found no such associations (2, 3). Our study differs from previous studies in that we only studied patients with severe pneumonia.…”
Section: Discussionmentioning
confidence: 92%
“…Studies on adults have reported the presence of RSV in between 6.1% and 10.0% of patients hospitalized with respiratory symptoms [22],[24]. RSV infection in community-acquired pneumonia (CAP) pediatric cases varies between 19.8% and 30.5% [25],[26] and it is estimated at about 3.8% in adults [27]. Approximately half of the cases of RSV-induced CAP in children ?3 years of age present with co-infection from other viral agents.…”
Section: Resultsmentioning
confidence: 99%